2007
DOI: 10.1007/s00449-007-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neuro-fuzzy modelling of anaerobic digestion of primary sedimentation sludge

Abstract: Modelling of anaerobic digestion systems is difficult because their performance is complex and varies significantly with influent characteristics and operational conditions. In this study, Adaptive Neuro-Fuzzy Inference System (ANFIS) were used for modelling of anaerobic digestion system of primary sludge of Kayseri municipal WasteWater Treatment Plant (WWTP). Effluent Volatile Solid (VS) and methane yield were predicted by the ANFIS. Two stage models were performed. In the first stage, effluent VS concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…The input of the data included the input data and output data in the form of a data array (Chen et al 2010(Chen et al : 1187. The final action at this stage involved defining and partitioning the universe of discourse for the input variables using the subtractive clustering method (Cakmakci 2007;Wei et al 2011). The next step involved is generating the fuzzy inference system (FIS) (Chen et al 2010;Efendigil et al 2009).…”
Section: Anfis Processmentioning
confidence: 99%
“…The input of the data included the input data and output data in the form of a data array (Chen et al 2010(Chen et al : 1187. The final action at this stage involved defining and partitioning the universe of discourse for the input variables using the subtractive clustering method (Cakmakci 2007;Wei et al 2011). The next step involved is generating the fuzzy inference system (FIS) (Chen et al 2010;Efendigil et al 2009).…”
Section: Anfis Processmentioning
confidence: 99%
“…It was found that the prediction performances of ANFIS model is better than traditional multiple linear regression model. ANFIS has also been used in the field of science and technology by many researchers (Guler & Ubeyli, 2004; Zaheeruddin & Garima, 2006; Naadimutha et al, 2007;Cakmakci, 2007;Bakhtyar et al, 2008;Wang & Elhag, 2008;Khajeh et al, 2009;Radulovic & Rankovic, 2010;Yan et al, 2010;Ata & Kocyigit, 2010;Sargolzaei & Kianifar, 2010;Yilmaz & Kaynar, 2011;Mohammadi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The normalized data are divided into 126 samples for training and 14 samples for testing of the model. A large percentage of the data set should be used during the training stage since ANFIS is quite adapted nonlinear functional dependency between the influent and effluent variables [10]. This could also result in avoiding the problem of over fitting, which led to large testing error.…”
Section: Anfis Model Implementationmentioning
confidence: 99%